A colorimetric and fluorescence lighting-up probe for the determination of biogenic primary diamine during the spoilage of fish. (February 2021) - Zhu, Beitong; Jiang, Lirong; Chen, Tianhong; Bao, Guang-Ming; Zeng, Lintao; Hu, Xichao; Yuan, Hou-Qun
Abstract: Biogenic primary diamines are a family of critical food spoilage biomarkers. To maintain food safety, it is necessary to implement highly efficient detection methods to monitor the levels of biogenic primary diamines in edible products. In this study, we report a 7-diethylaminocoumarin derivative, CMA-Cl, as a colorimetric and fluorescence lighting-up probe for detecting critical biogenic primary diamines including cadaverine and putrescine. The CMA-Cl probe underwent a nucleophilic substitution and condensation reaction with biogenic primary diamines, generating highly emissive compounds, which displayed strong emission at 475 nm with a fluorescence quantum yield of 36.4%. The CMA-Cl probe showed colorimetric and fluorescence dual-response towards biogenic primary amines with a significant linear relationship, good selectivity, and low limit of detection (209 nM). The probe demonstrated a good recovery (97–122%) for the determination of a typical biogenic primary diamine cadaverine during the spoilage of fish. Furthermore, CMA-Cl -loaded paper was fabricated for the real-time visual detection of a typical biogenic primary diamine cadaverine in fish samples based on distinct changes in color and fluorescence. Graphical abstract: Image 1 Highlights: CMA-Cl was devised as a fluorescence probe for detecting biogenic primary diamine. The probe showed colorimetric and fluorescence dual-response towards biogenic primary diamine. The probe demonstrated good recovery for the determination of biogenic primary diamine from the spoilage of fish. CMA-Cl test paper was fabricated for visual detection of biogenic primary diamine from the spoilage of fish.